Analysis of the positive results and influencing factors of hepatitis B antibody in hospitalized neonates with AgHBs positive mothers - Min, Yu xiao; Gao, Ying; Liu, Chun tian; Lu, Xiao yu; Chen, Xiao chun (Frontiers in Pediatrics, 2022)
Purpose To investigate the results of positive antibody to hepatitis surface antigen(anti-HBs)in hospitalized neonates whose mothers were hepatitis B surface antigen (AgHBs) positive and to explore the influencing factors. Method The study subjects were hospitalized neonates whose mothers were positive for AgHBs. According to the serological test results of five immune markers of hepatitis B virus (HBV), they were divided into positive for anti-HBs and negative for anti-HBs. Retrospective analysis of relevant factors affecting results of anti-HBs. Result 269 cases (80.78%) were positive for anti-HBs and 64 cases (19.22%) were negative for anti-HBs. Univariate analysis results: the number of hepatitis B immunoglobulin (HBIG) injections after birth, whether HBIG was injected within 6 h, whether Hepatitis B vaccine (Hep B) was injected within 6 h, whether combined immunization within 12 h, whether Hep B was vaccinated on time after discharge, whether preterm birth, and whether low birth weight infants were statistically significant (P < 0.05). The results of binary logistic regression analysis: HBIG injection time ≤6 h (OR = 0.213), combined immunization time ≤12 h (OR = 0.024) were protective factors; premature infants (OR = 7.175), ALB/GLO (OR = 9.792) and failure to complete three vaccinations on time (OR = 12.659) were risk factors (P < 0.05). Conclusion Although China has implemented a national immunization program, vaccination of hospitalized neonates whose mothers are positive for AgHBs has not been effective. Therefore, it is recommended to strengthen training for medical staff and families to ensure that neonates can complete the three doses of vaccination on time after discharge from the hospital and to strengthen follow-up for premature infants.